Reviewing Theoretical and Numerical Models for PCM-embedded Cementitious Composites - Antonio Caggiano; Christoph Mankel; Eddie Koenders (Buildings, 2018)
Accumulating solar and/or environmental heat in walls of apartment buildings or houses is a way to level-out daily temperature differences and significantly cut back on energy demands. A possible way to achieve this goal is by developing advanced composites that consist of porous cementitious materials with embedded phase change materials (PCMs) that have the potential to accumulate or liberate heat energy during a chemical phase change from liquid to solid, or vice versa. This paper aims to report the current state of art on numerical and theoretical approaches available in the scientific literature for modelling the thermal behavior and heat accumulation/liberation of PCMs employed in cement-based composites. The work focuses on reviewing numerical tools for modelling phase change problems while emphasizing the so-called Stefan problem, or particularly, on the numerical techniques available for solving it. In this research field, it is the fixed grid method that is the most commonly and practically applied approach. After this, a discussion on the modelling procedures available for schematizing cementitious composites with embedded PCMs is reported.